Establishing diagnostic criteria for occult hepatitis B virus infections in community based populations. Issue 1 (16th October 2013) - Minuk, Gerald Y.; Huynh, Chris; Uhanova, Julia; Osiowy, Carla
Abstract Present diagnostic criteria for occult hepatitis B virus (HBV) infection requires blood or liver samples to test positive for at least two HBV DNA targets in hepatitis B surface antigen (HBsAg) negative individuals. These criteria were derived from studies involving referred or selected patient populations. The objective of the present study was to determine whether the present definition of occult HBV infection also applies within a nonselected community based population. HBV DNA testing was performed in 1, 007 HBsAg negative sera by real time PCR with primer sets targeting the Enhancer I (ENHI), precore/core and surface/polymerase (S) genomic regions. Real time PCR positive cases were analyzed further by nested PCR. The results were then correlated with serologic findings among HBV DNA negative and occult positive individuals. Fifty‐five sera (5.5%) were positive for at least one of the three genomic regions. Positive results with at least two primer/probe sets (thereby satisfying present diagnostic criteria for occult HBV infection) were identified in 8 (0.8%) samples (3 ENHI plus S, 2 ENHI plus precore/core and 3 having positive results with all three primer/probe sets). The prevalence of HBV serologic markers in samples that tested positive for only one primer set were similar to those of HBV DNA negative matched controls, thereby arguing against their representing occult infection. The results of this study suggest that the present diagnostic criteria for occult HBV infection are also appropriate for population based studies. However, further studies are required to confirm that impression. J. Med. Virol. 86:156–161, 2014. © 2013 Wiley Periodicals, Inc.